Gomphrena globosa Common Globe Amaranth: FPS-234/FP234, 5/2007 - Gilman, Edward; Howe, Teresa (EDIS, 2007)
This document provides an overview of the common globe amaranth (Gomphrena globosa), detailing its characteristics, planting requirements, and uses. The plant is described as an annual with globe-shaped flowers in various colors, commonly used in mass plantings, rock gardens, and containers. It thrives in full sun and moderately dry soil, showing resistance to heat and minimal pest issues. The document also outlines its growth habits, including height, spread, and leaf arrangement, and notes its availability and non-invasive status. Propagation is typically by seed, and the plant is noted for its drought tolerance and suitability for areas with limited irrigation. Original publication date October 1999.